Analysis and compact modeling of temperature-dependent switching in SiC IGBT circuits. (March 2019) - Matsuura, Kai; Tanimoto, Yuta; Saito, Atsushi; Miyaoku, Yosuke; Mizoguchi, Takeshi; Miura-Mattausch, Mitiko; Mattausch, Hans Jürgen
Highlights: Strong measured temperature-dependent switching of 4H-SiC IGBT verified. Mayor reason is temperature-dependent carrier trapping in MOSFET part of IGBT. Carrier trapping modeled as threshold-voltage shift and oxide-charge modification. Switching tail is increased by temperature-dependent carrier lifetime in IGBT base. New compact model accurately reproduces temperature-dependent SiC IGBT switching. Abstract: Compact modeling of the 4H-SiC IGBT switching characteristics in circuits is investigated, with a focus on reproducing the temperature-dependent switching performance. For this purpose the HiSIM-IGBT compact model for circuit simulation, previously developed for Si as well as SiC IGBTs, is extended by replacing the physical Si material parameters with those of SiC. Using this extended model, good reproduction of measured 4H-SiC IGBT switching waveforms at room temperature has been confirmed. However, substantial deviations are observed between measured and simulated switching characteristics at higher temperatures. The main reason is identified in the reported analysis as the temperature dependence of the carrier trapping, which strongly influences the characteristics of the MOSFET part in the IGBT. This carrier trap effect is phenomenologically modeled by a threshold voltage shift as well as a charge modification induced at the gate oxide. An important further effect is induced by the temperature dependence of the carrier lifetime in the base region, which mainly affects the bipolar IGBT part and increases the switching-tail current at higher temperatures. It is demonstrated that the newly developed compact model can accurately reproduce the measured SiC IGBT switching performances for a wide range of temperature variations, which enables a reliable and accurate design of SiC-IGBT circuits.